Latar Belakang Historis dan Teologis Sakramen Pernikahan di dalam Gereja - Pan Djun Tjhong (Voice, 2021)
The sacrament of marriage which begins with premarital guidance in the church is considered as a must by the Christian community in general and prospective married couples and also their families in particular. The sacrament of marriage is considered as an important process of validation that incorporate a condition of ontological union. It is taken for granted without and has never been questioned why such a personal and familial event based on love should be endorsed by the church even though there is no solid evidence in the Bible for this. The church's sacrament of marriage is not proven exist in the Bible. The marriage certificate issued by the church as the product of marriage sacrament is made the initial condition of whether a marriage is legal or not to proceed to civil registration. library research of several marriage historical literature and descriptive theological exposition of some key biblical passage about marriage have been done in order to give some insight to the church members about what has so far been done regarding the marriage sacrament.